The Relationship Between Citizen Oversight and Procedural Justice Measures in Policing: An Exploratory Study - Holliday, Bradley S. (American journal of criminal justice, 2022)
Some American law enforcement agencies continue to experience disruptions in the level of trust and legitimacy ascribed to them by their communities. Citizen review boards (CRBs), may be an effective means for improving the police-community relationship. Utilizing a framework grounded in procedural justice and citizen participation, this study examines whether a link exists between CRBs and community satisfaction in the police and four procedural justice measures: 1) trust in the police, 2) belief the police are held accountable, 3) belief the police treat all people equally, and 4) belief the police are building positive community relationships. To estimate these correlations, this study uses a unique dataset from 48 U.S. cities and employs bivariate and multivariate methods to analyze the data. The findings indicate a mostly positive association between CRBs and procedural justice measures, which suggests that CRBs may be able to bolster legitimacy and enhance the police-community relationship in some communities.